Futuristic perception and carrier aspects of nursing profession among nursing students at Kalaburagi city, Karnataka - Motakpalli, Kaviraj; Shaheen, Shahnaz; Jamadar, Deepak; Bendigeri, N. D. (International Journal Of Community Medicine And Public Health, 2018)
Background: The nursing profession is one of the important and integral parts of health care delivery system. Hence nursing profession is rated as one of the most trusted profession in the health care industry and also considered as one of the exiting and in demand profession. Our study aims to know the futuristic perception of young and dynamic students of nursing colleges across the Kalaburagi city. As nursing profession is a supporting pillar for the health care sector. It is very important to understand the significant social professional values and the urge and intense of our nursing students at this region and time. Methods: A descriptive cross-sectional study design was used to identify the nursing students’ attitudes toward nursing profession. The study was carried out in 240 nursing students in different nursing colleges at Kalaburagi city. Results: Only 27.9% students had family members or relatives in the nursing profession. The reasons for joining nursing revealed 80.42% students were self motivated to perceive nursing as a carrier. Regarding perception 97.08% perceived nursing as an opportunity to serve humanity and 92.52% perceive nursing as a caring profession. Conclusions: Though nursing is regarded as a caring, dignify and respectful profession still many don’t want to work locally. More than half of the students were interested to work in abroad.